PENINGKATAN KETERAMPILAN PENANGANAN PASIEN GAWAT DARURAT MELALUI PELATIHAN BASIC TRAUMA CARDIAC LIFE SUPPORT (BTCLS) DI AKADEMI KEPERAWATAN KESDAM SIANTAR - Anwar, Syahferi; Tanjung, Dudut; Ismayadi, Ismayadi; Damanik, Balqis Nurmauli; Pulungan, Ruslan Zuhair (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
This community service project aims to enhance emergency handling competencies through Basic Trauma Cardiac Life Support (BTCLS) training at Akademi Keperawatan KESDAM Siantar. The activity was implemented using a participatory and intensive simulation-based approach that integrated theoretical instruction with practical field exercises over a six-day period. Evaluations conducted through pre-test and post-test assessments revealed an average knowledge score increase from 45.5 to 85.5 (an improvement of 87.91%) and an average skill score of 85. The utilization of resuscitation manikins and realistic emergency simulations significantly improved participants’ response speed and accuracy in critical situations. These results demonstrate the effectiveness of simulation-based training in enhancing emergency response quality, as well as boosting the confidence and professionalism of healthcare personnel. The contributions of this project to the advancement of nursing education serve as a benchmark for other institutions aiming to implement similar training programs to address modern challenges Keywords: BTCLS, Training, Service, Competence, Nursing